Cinderella goes to work: the new woman of Mike Nichols’s "Working girl" - Induráin Eraso, Carmen (Huarte de San Juan. Filología y Didáctica de la Lengua, 1999)
This paper analyses the representation of US American working women in a sample comedy of the 1990s: Mike Nichols’s “Working Girl” (1988). Throughout this film we will witness its female lead undergoing a double male dominance. Sexually harassed in the workplace and regarded as a sexual commodity at home she will only reach professional status after rejecting her working class condition and abating her allotted feminine complaisance to patriarchal rules. Despite this witty comedy’s presentation of a positive, strong heroine finally succeeding both in the labour and personal spheres, a deeper reading of this fi l m proves less optimistic since presenting women’s success as workers as inevitably linked to not only heterosexual romance, but also women’s sexual performance and their integration in the capitalist structure, therefore closely dependent on gender and social class.